If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -3x = 8 + 2 Combine like terms: 8 + 2 = 10 -7 + -3x = 10 Solving -7 + -3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3x = 10 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = 10 + 7 -3x = 10 + 7 Combine like terms: 10 + 7 = 17 -3x = 17 Divide each side by '-3'. x = -5.666666667 Simplifying x = -5.666666667
| 4x+x-3x+7=2x+x | | 8(x+.5)=2x+4 | | -5(2x-9)=2(x-8) | | 4x^2-10=-6x | | 2c+4-3c=-9+c+15 | | 7C+1=50 | | x-4.5=3 | | 10.6p+15=205.8 | | 10=50x | | 8s-12=52 | | -x-3x+20=x | | 3xyz-y+4x-y= | | 45p=168 | | 2f-81=11 | | 27=x+14 | | -36-9x=-12x+3 | | (5x-2)(7x+8)= | | 2(1/2x+1)=-3(2x-1)+4(2x+1) | | -8x+-3x= | | 2x=3x-22 | | 3r-7=17r | | 400p+20=680 | | 2x+x+2x=126 | | 32.8=8n | | 9s=-20 | | (-3+2i)-(4-4i)= | | 7-2p=12p | | (8x^2-3x^3)-(2x^2-5x^3)= | | 4x+14=-3x | | 7(4+h)h=9 | | -3x+2x+9y-2x= | | 5n+3=2(n+2)-3m |